Threatening faces induce fear circuitry hypersynchrony in soldiers with post-traumatic stress disorder. Issue 1 (January 2016) - Dunkley, Benjamin T; Pang, Elizabeth W; Sedge, Paul A; Jetly, Rakesh; Doesburg, Sam M; Taylor, Margot J
Abstract: Background: Post-traumatic stress disorder (PTSD) is associated with atypical responses to emotional face stimuli with preferential processing given to threat-related facial expressions via hyperactive amygdalae disengaged from medial prefrontal modulation. Method: We examined implicit emotional face perception in soldiers with (n = 20) and without (n = 25) PTSD using magnetoencephalography to define spatiotemporal network interactions, and a subsequent region-of-interest analysis to characterize the network role of the right amygdala and medial prefrontal cortex in threatening face perception. Results: Contrasts of network interactions revealed the PTSD group were hyperconnected compared to controls in the phase-locking response in the 2–24 Hz range for angry faces, but not for happy faces when contrasting groups. Hyperconnectivity in PTSD was greatest in the posterior cingulate, right ventromedial prefrontal cortex, right parietal regions and the right temporal pole, as well as the right amygdala. Graph measures of right amygdala and medial prefrontal connectivity revealed increases in node strength and clustering in PTSD, but not inter-node connectivity. Additionally, these measures were found to correlate with anxiety and depression. Conclusions: In line with prior studies, amygdala hyperconnectivity was observed in PTSD in relation to threatening faces, but the medial prefrontal cortex also displayed enhanced connectivity in our network-based approach. Overall, these results support preferential neurophysiological encoding of threat-related facial expressions in those with PTSD.